A Heuristic Algorithm and Simulation Approach to Relative Location of Facilities - Armour, Gordon C.; Buffa, Elwood S. (Management Science, 1963)
This paper presents a new methodology for determining suboptimum relative location patterns for physical facilities. It presents a computer program governed by an algorithm which determines how relative location patterns should be altered to obtain sequentially the most improved pattern with each change, commands their alteration, evaluates the results of alterations, and identifies the sub-optimum relative location patterns. 3 The computer output yields a block diagramatic layout of the facility areas, and the areas need not be equal. 4 A manufacturing plant layout example is used because the methodology is well illustrated by reference to some kind of example, and this one is commonly known. The methodology itself, however, is general in nature and not restricted to such applications.